Is vaginal breech delivery safe option?: Analysis of 50 vaginal breech delivery in Zainoel Abidin and Ibu Anak Hospital Banda Aceh in 2011 - Eva Febia; Mohammad Andalas (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
There were conflicting results about the success of vaginal breech delivery. Descriptive data about the success of vaginal breech delivery was needed in every institution. This research was conducted in Zainoel Abidin and Ibu Anak Hospital, Banda Aceh in order to analyze the success of vaginal breech delivery as well as the outcome of mother and babies. There were 50 vaginal breech deliveries in Zainoel Abidin Hospital during the study. The success of vaginal breech delivery was determined by the outcome of babies, the perinatal mortality and Apgar score of the babies. Vaginal breech delivery was more likely successful for babies whose birth weight 2000-3000 grams, between 35-40 weeks of gestational age, and singleton. Factors support the increase likelihood for the success of vaginal birth were adequate amniotic fluid, multiparity, and previously bigger baby that was delivered vaginally. We conclude that factors contribute the success of vaginal breech delivery were influenced by the birth weight, gestational age, parity, and amniotic fluid volume. However, since the number of subject was limited, further study with bigger sample size was needed